Immobilized CdS quantum dots in spherical polyelectrolyte brushes: fabrication, characterization and optical properties. Issue 15 (9th March 2015) - Cang, Yu; Zhang, Rui; Shi, Guixin; Zhang, Jianchao; Liu, Lixiao; Hou, Xiaoyan; Yu, Zhenchuan; Fang, Dingye; Guo, Xuhong
Abstract : The SPB@CdS nanoparticles exhibit controllable and reversible photoluminescence with pH as a trigger and strong photochemical stability in basic solution. Abstract : In this work, we demonstrated a facile and environmentally friendly method of preparing water-soluble cadmium sulfide (CdS) quantum dots (QDs) immobilized in spherical polyelectrolyte brushes (SPBs). The synthesis included three stages as follows: preparation of SPBs, introduction of Cd 2+ by the ion-exchange process and in situ fabrication of CdS in SPBs. The X-ray diffraction (XRD) pattern and the transmission electron microscopy (TEM) images proved that the CdS nanocrystallines (NCs) were cubic in structure and well distributed in SPBs. The size and photoluminescence (PL) emission of hybrid nanoparticles (SPB@CdS) could be tailored by adjusting some parameters, such as pH of SPBs, the ratio of Cd/S, the temperature of reaction and dimensions of SPB@CdS. For instance, upon increasing the pH value of SPBs and the ratio of Cd/S, the trap emission of CdS NCs could be transformed into band-edge emission. And the PL emission shifted from 490 to 580 nm as the reaction temperature increased from 10 to 90 °C. More interesting was that the PL emission of SPB@CdS could be quenched and recovered reversibly by pH adjustment due to the pH sensitive chains of poly(acrylic acid) grafting from the polystyrene core. The SPB@CdS displayed excellent photochemical stability in visible light above pH 10 which provided a possibility for storing QDs in visible light. In addition, this simple method can be extended to other sulfide fabrication in SPBs, such as ZnS, which has also been successfully embedded in SPBs.